2011
DOI: 10.1111/j.1745-4565.2010.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbial Contamination Levels of Street‐vended Foods in Korea

Abstract: This study was conducted to evaluate the microbial quality of street‐vended foods in Korea. The microbiological contamination levels of aerobic mesophilic bacteria ranged from 0 to 7.43 log cfu/g with a mean value of 4.71 ± 1.53 log cfu/g, while the level of total coliforms ranged from 0 to 6.86 log cfu/g with a mean value of 3.24 ± 1.40 log cfu/g. Staphylococcus aureus (SA) and Escherichia coli (EC) were detected in 9% (mean value: 3.75 ± 0.56 log cfu/g) and 3% (mean value: 2.33 ± 0.90 log cfu/g) of 326 exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
3
14
4
Order By: Relevance
“…However, Meloni et al (28) found that 9.5% of RTE products were contaminated with L. monocytogenes. Mouspye and Von Holly (29), Cho et al (17), Rodriguez et al (31), and Balzaretti and Marzano (10) found neither Listeria spp. nor Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, Meloni et al (28) found that 9.5% of RTE products were contaminated with L. monocytogenes. Mouspye and Von Holly (29), Cho et al (17), Rodriguez et al (31), and Balzaretti and Marzano (10) found neither Listeria spp. nor Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…RTE foods can be defined as foods and beverages prepared and/ or sold by vendors on the street and in other public places for immediate consumption or consumption at a later time without further processing or preparation (Cho et al, 2011;Tsang, 2002). Due to socio-economic changes characterized by increased mobility, resulting in more RTE foods taken outside the home, food vendors' services are on the increase and responsibility for the food safety have been transferred from individuals/families to the food vendors who rarely enforce good manufacturing practices (Musa and Akande, 2002).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
“…Children tended to ignore the potential hazards associated with cooked snacks sold in snack bars, even though their high calorie content and poor nutritional value can cause children to become overweight/obese (Deckelbaum & Williams, 2001;Ebbeling, Pawlak, & Ludwig, 2002;Gillis & Bar-Or, 2003). These foods may also contain microbiological hazards (Cho et al, 2011).…”
Section: Discussionmentioning
confidence: 99%